The Development of Teaching Media Video Instructional Book at The Student Courses Technology Education, Faculty of Education, University State Makassar - Amir, Amir; Parumbuan, Mesach Dayunison (Universitas Negeri Makassar, 2018)
This study aims to develop and produce a video media development textbook to be used in lectures/learning courses on video media development for students of Educational Technology Study Program, Faculty of Education, Makassar State University. This type of research is research and development (R & D) with the Four-D (4D) development model by S. Thiagarajan and Semmel (1994). Research subjects included: experts in the field of study / content learning, learning media experts, textbook design experts, and students of Educational Technology Study Program. Data was recorded by questionnaire and test techniques. Data were analyzed by descriptive and quantitative qualitative statistics. The results showed that the video media development textbook developed with the Four D model (4D) met the criteria of valid, practical, and effective.